Streptavidin-coated gold nanoparticles: critical role of oligonucleotides on stability and fractal aggregation - D'Agata, Roberta; Palladino, Pasquale; Spoto, Giuseppe (Beilstein Journal of Nanotechnology, 2017)
Gold nanoparticles (AuNPs) exhibit unique properties that can be modulated through a tailored surface functionalization, enabling their targeted use in biochemical sensing and medical diagnostics. In particular, streptavidin-modified AuNPs are increasingly used for biosensing purposes. We report here a study of AuNPs surface-functionalized with streptavidin-biotinylated oligonucleotide, focussing on the role played by the oligonucleotide probes in the stabilization/destabilization of the functionalized nanoparticle dispersion. The behaviour of the modified AuNP dispersion as a consequence of the competitive displacement of the biotinylated oligonucleotide has been investigated and the critical role of displaced oligonucletides in triggering the quasi one-dimensional aggregation of nanoparticles is demonstrated for the first time. The thorough understanding of the fundamental properties of bioconjugated AuNPs is of great importance for the design of highly sensitive and reliable functionalized AuNP-based assays.
Keywords: biosensors; DNA; gold nanoparticles; nanoparticles aggregation; plasmonics; streptavidin

(untitled) - Daniel, M.-C.; Astruc, D. (Chem. Rev., 2004)

(untitled) - Howes, P. D.; Chandrawati, R.; Stevens, M. M. (Science, 2014)

(untitled) - Giljohann, D. A.; Seferos, D. S.; Daniel, W. L.; Massich, M. D.; Patel, P. C.; Mirkin, C. A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Zanoli, L. M.; D’Agata, R.; Spoto, G. (Anal. Bioanal. Chem., 2012)

(untitled) - Bellassai, N.; Spoto, G. (Anal. Bioanal. Chem., 2016)

(untitled) - Pérez-López, B.; Merkoçi, A. (Anal. Bioanal. Chem., 2011)

(untitled) - Saha, K.; Agasti, S. S.; Kim, C.; Li, X.; Rotello, V. M. (Chem. Rev., 2012)

(untitled) - Golden, M. S.; Bjonnes, A. C.; Georgiadis, R. M. (J. Phys. Chem. C, 2010)

(untitled) - Zeng, S.; Yu, X.; Law, W.-C.; Zhang, Y.; Hu, R.; Dinh, X.-Q.; Ho, H.-P.; Yong, K.-T. (Sens. Actuators, B, 2013)

(untitled) - Spoto, G.; Minunni, M. (J. Phys. Chem. Lett., 2012)

(untitled) - D’Agata, R.; Corradini, R.; Grasso, G.; Marchelli, R.; Spoto, G. (ChemBioChem, 2008)

(untitled) - D’Agata, R.; Corradini, R.; Ferretti, C.; Zanoli, L.; Gatti, M.; Marchelli, R.; Spoto, G. (Biosens. Bioelectron., 2010)

(untitled) - D’Agata, R.; Breveglieri, G.; Zanoli, L. M.; Borgatti, M.; Spoto, G.; Gambari, R. (Anal. Chem., 2011)

Detection of non-amplified genomic DNA - Spoto, G.; Corradini, R. (Springer, 2012)

(untitled) - Zhou, W.; Gao, X.; Liu, D.; Chen, X. (Chem. Rev., 2015)

(untitled) - Geneviève, M.; Vieu, C.; Carles, R.; Zwick, A.; Brière, G.; Salomé, L.; Trévisiol, E. (Microelectron. Eng., 2007)

(untitled) - Cobbe, S.; Connolly, S.; Ryan, D.; Nagle, L.; Eritja, R.; Fitzmaurice, D. (J. Phys. Chem. B, 2003)

(untitled) - Niemeyer, C. M.; Ceyhan, B.; Noyong, M.; Simon, U. (Biochem. Biophys. Res. Commun., 2003)

(untitled) - Niemeyer, C. M.; Ceyhan, B.; Hazarika, P. (Angew. Chem., Int. Ed., 2003)

(untitled) - Verma, R.; Crocker, J. C.; Lubensky, T. C.; Yodh, A. G. (Macromolecules, 2000)

(untitled) - Asakura, S.; Oosawa, F. (J. Chem. Phys., 1954)

(untitled) - Asakura, S.; Oosawa, F. (J. Polym. Sci., 1958)

(untitled) - Vrij, A. (Pure Appl. Chem., 1976)

(untitled) - Joanny, J. F.; Leibler, L.; de Gennes, P. G. (J. Polym. Sci., Polym. Phys. Ed., 1979)

(untitled) - Jenkins, P.; Snowden, M. (Adv. Colloid Interface Sci., 1996)

(untitled) - Mahmoudi, M.; Lynch, I.; Ejtehadi, M. R.; Monopoli, M. P.; Baldelli Bombelli, F.; Laurent, S. (Chem. Rev., 2011)

(untitled) - Brewer, S. H.; Glomm, W. R.; Johnson, M. C.; Knag, M. K.; Franzen, S. (Langmuir, 2005)

(untitled) - Häussling, L.; Michel, B.; Ringsdorf, H.; Rohrer, H. (Angew. Chem., Int. Ed. Engl., 1991)

(untitled) - Weber, P. C.; Ohlendorf, D. H.; Wendoloski, J. J.; Salemme, F. R. (Science, 1989)

(untitled) - Anker, J. N.; Hall, W. P.; Lyandres, O.; Shah, N. C.; Zhao, J.; Van Duyne, R. P. (Nat. Mater., 2008)

(untitled) - Pollitt, M. J.; Buckton, G.; Piper, R.; Brocchini, S. (RSC Adv., 2015)

(untitled) - Templeton, A. C.; Pietron, J. J.; Murray, R. W.; Mulvaney, P. (J. Phys. Chem. B, 2000)

(untitled) - Hale, G. M.; Querry, M. R. (Appl. Opt., 1973)

(untitled) - Reiter, R.; Motschmann, H.; Knoll, W. (Langmuir, 1993)

(untitled) - De Feijter, J. A.; Benjamins, J.; Veer, F. A. (Biopolymers, 1978)

(untitled) - Rodrıguez-Fernández, J.; Pérez-Juste, J.; Liz-Marzán, L. M.; Lang, P. R. (J. Phys. Chem. C, 2007)

(untitled) - Eimer, W.; Williamson, J. R.; Boxer, S. G.; Pecora, R. (Biochemistry, 1990)

(untitled) - Park, S.; Brown, K. A.; Hamad-Schifferli, K. (Nano Lett., 2004)

(untitled) - Bantz, C.; Koshkina, O.; Lang, T.; Galla, H.-J.; Kirkpatrick, C. J.; Stauber, R. H.; Maskos, M. (Beilstein J. Nanotechnol., 2014)

(untitled) - Chilkoti, A.; Stayton, P. S. (J. Am. Chem. Soc., 1995)

(untitled) - Pérez-Luna, V. H.; O’Brien, M. J.; Opperman, K. A.; Hampton, P. D.; López, G. P.; Klumb, L. A.; Stayton, P. S. (J. Am. Chem. Soc., 1999)

(untitled) - Chilkoti, A.; Boland, T.; Ratner, B. D.; Stayton, P. S. (Biophys. J., 1995)

(untitled) - Klumb, L. A.; Chu, V.; Stayton, P. S. (Biochemistry, 1998)

(untitled) - Jung, L. S.; Nelson, K. E.; Stayton, P. S.; Campbell, C. T. (Langmuir, 2000)

(untitled) - D’Agata, R.; Grasso, G.; Spoto, G. (Open Spectrosc. J., 2008)

(untitled) - Duan, X.; Li, Y.; Rajan, N. K.; Routenberg, D. A.; Modis, Y.; Reed, M. A. (Nat. Nanotechnol., 2012)

(untitled) - Broder, G. R.; Ranasinghe, R. T.; Neylon, C.; Morgan, H.; Roach, P. L. (Anal. Chem., 2011)

(untitled) - de Vasconcelos, C. L.; Pereira, M. R.; Fonseca, J. L. C. (J. Dispersion Sci. Technol., 2005)

(untitled) - Storhoff, J. J.; Lazarides, A. A.; Mucic, R. C.; Mirkin, C. A.; Letsinger, R. L.; Schatz, G. C. (J. Am. Chem. Soc., 2000)

(untitled) - Nelson, E. M.; Rothberg, L. J. (Langmuir, 2011)

(untitled) - Michen, B.; Geers, C.; Vanhecke, D.; Endes, C.; Rothen-Rutishauser, B.; Balog, S.; Petri-Fink, A. (Sci. Rep., 2015)

(untitled) - Chegel, V.; Rachkov, O.; Lopatynskyi, A.; Ishihara, S.; Yanchuk, I.; Nemoto, Y.; Hill, J. P.; Ariga, K. (J. Phys. Chem. C, 2012)

(untitled) - Tisserant, J.-N.; Reissner, P. A.; Beyer, H.; Fedoryshyn, Y.; Stemmer, A. (Langmuir, 2015)

(untitled) - Liao, J.; Zhang, Y.; Yu, W.; Xu, L.; Ge, C.; Liu, J.; Gu, N. (Colloids Surf., A, 2003)

(untitled) - Zhang, X.; Servos, M. R.; Liu, J. (Langmuir, 2012)

(untitled) - Li, H.; Rothberg, L. J. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Li, H.; Rothberg, L. J. (J. Am. Chem. Soc., 2004)

(untitled) - Brown, K. A.; Park, S.; Hamad-Schifferli, K. (J. Phys. Chem. C, 2008)

(untitled) - Link, S.; El-Sayed, M. A. (Int. Rev. Phys. Chem., 2000)

(untitled) - Weisbecker, C. S.; Merritt, M. G.; Whitesides, G. M. (Langmuir, 1996)

(untitled) - Kalodimos, C. G.; Biris, N.; Bonvin, A. M. J. J.; Levandoski, M. M.; Guennuegues, M.; Boelens, R.; Kaptein, R. (Science, 2004)

(untitled) - Agback, P.; Baumann, H.; Knapp, S.; Ladenstein, R.; Härd, T. (Nat. Struct. Biol., 1998)

(untitled) - Florescu, A.-M.; Joyeux, M. (J. Chem. Phys., 2009)

(untitled) - Turkevich, J.; Stevenson, P. C.; Hillier, J. (Discuss. Faraday Soc., 1951)

(untitled) - El-Sayed, I. H.; Huang, X.; El-Sayed, M. A. (Cancer Lett., 2006)

(untitled) - Kumar, S.; Gandhi, K.; Kumar, R. (Ind. Eng. Chem. Res., 2007)